PENGARUH GROWTH OPPORTUNITY, KEPEMILIKAN MANAJERIAL, DAN RISIKO LITIGASI TERHADAP KONSERVATISME AKUNTANSI : (Studi Empiris Pada Perusahaan Sub Sektor Transportasi dan Logistik yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023) - Syara Syahidah; Farah Latifah Nurfauziah Farah Latifah Nurfauziah; Fitria Ningrum Sayekti Fitria Ningrum Sayekti; Dhea Amalea Dhea Amalea (Prodi Akuntansi, 2024)
This study focuses on the problem of accounting conservatism as measured by CONNAC value. The objectives of this study are, 1. To determine the effect of growth opportunity on accounting conservatism, 2. To determine the effect of managerial ownership on accounting conservatism, 3. To determine the effect of litigation risk on accounting conservatism, 4. To determine the growth opportunity, managerial ownership, and litigation risk on accounting conservatism in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This research uses quantitative methods, data collection techniques using documentation. The data used in this study are secondary data and sample selection using purposive sampling. Based on the results of purposive sampling from 37 companies, 12 transportation and logistics companies were obtained that met the sample criteria. The analysis technique used is descriptive analysis, classical assumption test and hypothesis testing. The results of this study simultaneously show that growth opportunity, managerial ownership and litigation risk affect accounting conservatism. However, partially only growth opportunity and managerial ownership have an effect on accounting conservatism. keywords : Growth Opportunity, Manajerial Ownership, Litigation Risk, and Conservatism Accounting